Sentiment analysis for Bangla microblog posts - Shaika, Chowdhury; Chowdhury, Wasifa (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2014.